Problems in Implementing the Principle of Horizontal Separation in Cases of Abandoned Land According to Presidential Regulation (Perpres) Number 62 of 2023 and Efforts to Resolute It - Akh Mulyanto; Azis Budianto (Greenation Research & Yayasan Global Resarch National, 2025)
The principle of horizontal separation is a fundamental principle in the Indonesian land law system, which states that land rights are separate from rights to objects located above or below it, as stipulated in Law Number 5 of 1960 concerning Agrarian Principles (UUPA). However, the implementation of Presidential Regulation Number 62 of 2023 concerning the Management of Abandoned Land has not fully accommodated this principle. This Presidential Regulation focuses on the repossession of land that is not being utilized according to its intended purpose, but does not explicitly regulate the protection of rights to buildings, plants, or other permanent objects standing on the land. As a result, legal problems arise, including potential conflicts between land rights holders and building owners, unclear objection mechanisms, and a lack of norms regarding civil rights over objects on abandoned land. This research employs a normative legal method, using a statutory regulatory and a conceptual approach. The analysis results reveal a lack of synchronization between the UUPA as the parent law and the latest implementing provisions, which has an impact on legal uncertainty and potential constitutional rights violations. Therefore, regulatory harmonization is necessary through the adoption of implementing regulations that prioritize protection for owners of immovable property, as well as the development of administrative and judicial dispute resolution mechanisms. Cross-institutional collaboration is also crucial to creating a fair and operational legal framework for managing abandoned land